The Role of Data Integration and Stakeholder Collaboration in Improving Health System Performance - Faisal, Ahmad; Abdillah, Muhammad Rifqy Naufal (Sinergi International Journal of Logistics, 2025)
This narrative review examines the integration of health systems, the role of public-private partnerships, and the effectiveness of disease surveillance mechanisms in low- and middle-income countries (LMICs). The aim is to synthesize the current body of literature on these critical health system components, exploring both structural and operational barriers that hinder effective policy implementation. The review employs a narrative methodology, gathering evidence from peer-reviewed studies, policy evaluations, and systematic reviews. The results highlight the importance of inter-organizational coordination, data integration, and stakeholder engagement in improving health system performance. Moreover, the review identifies key systemic factors such as infrastructure quality, governance coherence, and data capacity as pivotal in determining the success of health interventions. The discussion underscores the need for integrated policy frameworks that align central and local health efforts, as well as the importance of community-based participatory governance in enhancing policy effectiveness. The review concludes by recommending strategies to overcome structural barriers, including digital health system integration and improved multi-sectoral coordination. Future research should focus on longitudinal studies and the integration of qualitative data to further inform policy-making and enhance system resilience.